Unbounded Orchestrations of Transducers for Manufacturing - Alechina, Natasha; Brázdil, Tomáš; De Giacomo, Giuseppe; Felli, Paolo; Logan, Brian; Vardi, Moshe Y. (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
There has recently been increasing interest in using reactive synthesis techniques to automate the production of manufacturing process plans. Previous work has assumed that the set of manufacturing resources is known and fixed in advance. In this paper, we consider the more general problem of whether a controller can be synthesized given sufficient resources. In the unbounded setting, only the types of available manufacturing resources are given, and we want to know whether it is possible to manufacture a product using only resources of those type(s), and, if so, how many resources of each type are needed. We model manufacturing processes and facilities as transducers (automata with output), and show that the unbounded orchestration problem is decidable and the (Pareto) optimal set of resources necessary to manufacture a product is computable for uni-transducers. However, for multitransducers, the problem is undecidable.